MiR-9-1 Suppresses Cell Proliferation and Promotes Apoptosis by Targeting UHRF1 in Lung Cancer. (September 2021) - Jia, Cheng-You; Xiang, Wei; Liu, Ji-Bin; Jiang, Geng-Xi; Sun, Feng; Wu, Jian-Jun; Yang, Xiao-Li; Xin, Rui; Shi, Yi; Zhang, Dan-Dan; Li, Wen; Zuberi, Zavuga; et al.
Lung cancer is listed as the most common reason for cancer-related death all over the world despite diagnostic improvements and the development of chemotherapy and targeted therapies. MicroRNAs control both physiological and pathological processes including development and cancer. A microRNA-9 to 1 (miR-9 to 1) overexpression model in lung cancer cell lines was established and miR-9 to 1 was found to significantly suppress the proliferation rate in lung cancer cell lines, colony formation in vitro, and tumorigenicity in nude mice of A549 cells. Ubiquitin-like containing PHD and RING finger domains 1 (UHRF1) was then identified to direct target of miR-9 to 1. The inhibition of UHRF1 by miR-9 to 1 causes G1 arrest and p15, p16, and p21 were re-expressed in miR-9 to 1 group in mRNA level and protein level. Silence of UHRF1 expression in A549 cells resulted in the similar re-expression of p15, p16, p21 which is similar with miR-9 to 1 infection. Therefore, we concluded that UHRF1 is a new target for miR-9 to 1 to suppress cell proliferation by re-expression of tumor suppressors p15, p16, and p21 mediated by UHRF1.